Judge Leonard Meyers Retirement Luncheon at Golden State Plaza Ballroom - Watkins, Howard::::::::: (1987)
Judge Stephen Henry looking at Judge Leonard Meyers about to kiss his wife Dorothy Meyers; wrapped gift by table